The features of structural-impurity ordering of interfaces in Ta₂O₅-p-Si heterostructures (exposed to microwave pretreatment and aging) induced by further microwave treatment - Kolyadina, E.Yu.; Konakova, R.V.; Matveeva, L.A.; Mitin, V.F.; Shynkarenko, V.V.; Atanassova, E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The effect of short-term microwave treatment (MT) on the electronic
properties of interface in the Ta₂O₅−SiOx−p-Si structures has been investigated. The
samples of two types were studied: check ones (batch I) and those exposed to previous
MT (batch II). The samples were aged (hold in air) at a temperature of ~300 K for two
years. After that, they were exposed to MT during 2, 4, 6 and 8 s. Both before and after
two-year aging and further MT, we measured, for all samples, the spectra of surfacebarrier
electroreflectance (SBER) and concentration depth profiles of the components in
the structure, as well as the radii of curvature of heterosystem from which the intrinsic
stress (IS) values were calculated. It was found that the transition energy Eg grows with
time of MT for both type samples. This corresponds to decrease of compressing ISs in
27 % in the check sample (with more number of defect) and by 11 % in that previously
exposed to MT. This fact indicates structural-impurity ordering of the Si−SiOx interface.
The surface quantum-dimensional effect occurred after MT. After two-year aging, energy
quantization was observed in the previously irradiated sample for 6 s and in the check
sample (with more number of defects) after MT for 8 s. The most probable mechanism of
improvement of the near-surface properties of SiOx−Si interface is discussed.